(untitled) (Research, Society and Development, 2022)
The research aimed to carry out an epidemiological survey comparing the cases of COVID-19 in moments before and after the electoral period in Brazil, pointing out the influences of the federal public administration in the increase in incidence and consequent mortality. This is a quantitative epidemiological study with a critical approach, based on secondary data from the Information and Notifiable Diseases System (SINAN) found in the Information Technology Department of the Unified Health System (DATASUS), whose data are from March to December 2020, and January to March 2021 were selected. We analyzed 12,748,747 confirmed cases of COVID-19 grouped in incidence by month in the period evaluated and compared them by the non-parametric Kruskal-Wallis method, where a P value <0.05 was considered statistically significant. The data from this study demonstrate the significant increase in cases of COVID-19 in Brazil, where in November (the month after the elections), there is an increase in notifications compared to the month of October, the increase becomes statistically significant from the month of December onwards, which is the drastic scenario in the following year. In summary, based on the data expressed, it can be concluded that the Brazilian electoral period was largely influential in the worsening of the pandemic in the country.